Science on social media - Derya Gürer; Judith Hubbard; Wendy Bohon (Communications Earth & Environment, 2023)
During the February 2023 Turkey-Syria earthquakes, people looked for explanations. As scientists, we did our best to share our knowledge in a way that reached and connected with people beyond the scientific community. We did this through communicating uncertainties, and by listening to and learning from our audiences’ questions, concerns, and ideas.